HEALTH-RELATED PHYSICAL FITNESS AMONG UNDERGRADUATE STUDENTS IN PHYSICAL EDUCATION - Mesquita, Camila Angélica Asahi; Turi-lynch, Bruna Camilo; Bergoc, Rodrigo Dutra; Maia, Rosana Lisboa; Amaral, Sandra Lia; Monteiro, Henrique Luiz (Universidade Estadual de Maringá, 2018)
ABSTRACT The aim of this study was to describe and analyze physical fitness of undergraduate students in Physical Education. The sample consisted of 110 women and 115 men. We evaluated weight, height, body mass index, percentage of body fat (BF), heart rate, systolic blood pressure (SBP), diastolic blood pressure, flexibility, strength and muscular endurance (ME). As main results we observed a higher percentage of women with body fat and ME above the ideal values ​​for age when compared to men (BF: 37% vs 4%, p = 0.001; ME: 32% vs 13%, p = 0.001), while there were more men with changes in SBP when compared with women (22% vs 6%, p = 0.001). In conclusion, male students had higher levels of physical fitness than women, and a significant portion of undergraduate students in Physical Education showed results different than normal for anthropometric, hemodynamic and performance variables.

RESUMO O objetivo desse estudo foi descrever e analisar o condicionamento físico de alunos de graduação do curso de Educação Física. A amostra foi composta por 110 mulheres e 115 homens. Foram avaliados peso, altura, índice de massa corpórea, percentual de gordura corporal (GC), frequência cardíaca em repouso (FCR), pressão arterial sistólica (PAS) e diastólica, flexibilidade, força e resistência muscular localizada (RML). Como principais resultados observou-se maior porcentagem de mulheres com gordura corporal e RML acima dos valores ideais para a idade quando comparados aos homens (GC: 37% vs 4%, p= 0,001; RML: 32% vs 13%, p= 0,001), enquanto houveram mais homens com alteração na PAS quando confrontado com mulheres (22% vs 6%, p= 0,001). Em conclusão, estudantes do sexo masculino apresentaram maiores níveis de aptidão física em relação às mulheres, e parcela expressiva de alunos de Educação Física apresentam alterações nos valores de referência à normalidade para variáveis antropométricas, hemodinâmicas e de desempenho motor.
APTIDÃO FÍSICA RELACIONADA À SAÚDE DE ALUNOS DE GRADUÇÃO EM EDUCAÇÃO FÍSICA
Keywords: Physical Fitness; Health Profile; Health. Students.; Aptidão física; Perfil de saúde; Saúde; Estudantes.